Zoning Policy, Indirect Discrimination, and the Constitutional Right to Quality Education in Pangkalpinang City - Zaini Ali; Yandi (Faculty of Law, University of Merdeka Malang, 2025)
The PPDB zoning policy, regulated through Permendikbud No. 1 of 2021, was designed to democratize access to public education by replacing merit-based competition with geographic proximity as the primary admission criterion. This study critically examines whether the policy fulfills the constitutional right to quality education guaranteed by Article 31 of the 1945 Constitution and Article 12(1)(b) of Law No. 39 of 1999 on Human Rights, with particular reference to its implementation in Pangkalpinang City. Employing a normative-empirical legal research design that integrates a statute approach, conceptual approach, and socio-juridical field investigation, this study analyzes the constitutional adequacy of the zoning framework and its operational reality. The findings reveal that the policy's exclusive reliance on domicile proximity, in a context of structurally unequal school quality distribution, generates indirect discrimination incompatible with the principle of substantive justice. In Pangkalpinang City, implementation is further compromised by systematic domicile manipulation, digital discrimination in online registration, inter-zonal infrastructure inequality, inadequate public socialization, and the complete absence of adaptive regional regulations. Evaluated against the UNESCO 4A framework, the policy fails the dimensions of accessibility, acceptability, and adaptability. This study concludes that fundamental policy reformulation premised on school quality equalization, affirmative provisions for vulnerable groups, and locally adaptive regulation is constitutionally necessary.